Archaeological research in a rural settlement in the Ayacucho Valley, Peru - Valdez, Lidio M. (2021)
The manner the urban center of Huari of the Peruvian central highlands was established is an important topic. However, the issue remains little discussed. Taking into consideration information gathered from a huarpa settlement that existed in what eventually became the periphery of Huari, we discuss the way Huari achieved a great transformation late during the Early Intermediate Period and early during the Middle Horizon. The evidence suggests that at the end of the Early Intermediate Period a series of huarpa settlements were deserted in what appears to be a very conflictive situation. The former inhabitants of the rural huarpa villages found their way into much larger and better protected settlements. In this manner, a considerable number of huarpa settlements, that were viable for centuries, were deserted as their inhabitants moved specific centers such as Huari.